The Role of Body Language in SLA - Attelisi, Abdulhameed Ali (جامعة الزيتونة - كلية التربية - بني وليد, 2015)
Employing body movements to convey messages is one of the human characteristics. We all use our body movements simultaneously with our speech when we want to communicate with others. Even blind people gesture when they communicate. Although researchers in different disciplines have not identified the nature of the relationship between speech and gesture, they all acknowledge the existence of this relationship; simply, because people all over the world use body language when they speak. This indicates that gesturing is a human behaviour and it is not a phenomenon that characterizes certain people or culture. However, in linguistics and SLA, few studies have focused on the importance of gesture as a means of communication that facilitates the process of learning and teaching. This essay attempts to highlight the importance of considering gestures in SLA studies. Throughout two sections different issues will be discussed. In section one, the literature that deals with the relationship between speech and gesture will be reviewed, whereas section two will focus on two key questions (a) what are the reasons behind the paucity of gesture research in SLA, and (b) to what extent that studying gesture is relevant to SLA?
Keywords: تعلم اللغة الإنجليزية -- اللغة الإنجليزية -- لغة الجسد